Quality Disclosures and Disappointment: Evidence from the Academy Nominations - Michelangelo Rossi; Felix Schleef (CESifo GmbH, 2024)
This study examines the unintended consequences of quality disclosures, focusing on how Academy Award nominations impact consumer satisfaction in the movie industry. Awards, certifications, and nominations typically signal high quality and increase consumer expectations. Yet, if the experience falls short of the expectation, they may also lead to disappointment. Using a novel dataset from Movie-Lens, we analyze user ratings for movies surrounding Academy Award nominations from 1995 to 2019. We employ a difference-in-differences framework and a recommendation-based matching approach to isolate the "disappointment effect" showing a significant decline in ratings for nominated movies post-nomination. This effect accounts for more than 7% of the pre-nomination rating gap between nominated and non-nominated films and is most pronounced among less experienced users. Our findings are validated with data from IMDb, where the effect is even more pronounced, likely due to groupthink and public review dynamics. By isolating disappointment from selection and supply side responses, this study offers insights into the dual-edged nature of quality signals and their implications for consumer welfare.
Keywords: D82; D83; D91; 330; quality disclosure; movie industry; expectation formation; disappointment